Physical and numerical modeling for the investigation of downstream scour caused by sudden blockage in circular and box culvert inlets - Saeed Gohari; Somayeh Karimpour (Journal of Applied Research in Water and Wastewater, 2025)
This paper presents a comprehensive experimental and numerical study using non-cohesive uniform sand (d50 = 2 mm). The study investigates the impact of local scour downstream of four model culverts with different barrel shapes and inlet blockage sizes. The results show that, for clear water scour, the shape and number of culvert barrels affect downstream scour geometry. The most affected parameters of scour hole geometry in blocked inlet culverts were the maximum scour depth near the walls (dswall) and the maximum scoured sediment volume (ζs). The dswall ⁄ D values of rectangular model culverts were 1.3 to 1.5 times greater than those of circular model culverts. The results showed that the effect of inlet obstruction on dsmax is contingent on flow and culvert conditions. Based on this, a suitable relationship was proposed to estimate the maximum scour depth for each cross-section. The presented equations were compared to the existing equation based on inlet blockage by applying collected datasets and they showed superior performance. The comparison indicated that over 80% of the predicted values fall within ±30% error lines.